Rereading power and freedom in J.S. Mill - Baum, Bruce David, 1960- (University of Toronto Press, 2000)
In his canonical text, "On Liberty", the English philosopher and social reformer John Stuart Mill (1806-73) looked at the limits imposed by society and the state on individual freedom. Over one hundred years later, Bruce Baum, in "Rereading Power and Freedom in J.S. Mill," shows how important aspects of Mill's theory of freedom have been misinterpreted. The author recovers lost dimensions of Mill's thought, and in so doing, contributes to a critical sociology of freedom for our time. Drawing on Mill's thoughts on liberty and power scattered throughout his numerous texts on related subjects, Baum moves beyond what Mill has to say about freedom in "On Liberty." Baum discovers a consistent purpose behind Mill's advocacy of women's rights, universal suffrage, parliamentary and educational reforms, and workers' co-operatives. Whereas Mill is commonly interpreted as an advocate of negative liberty, Baum argues that Mill possesses a complex theory of freedom that unifies the pursuit of personal autonomy with the quest for collective self-determination through an egalitarian, genuinely participatory democratic politics. This insightful work traces new connections between Mill's liberalism and the later revisionist liberalisms of theorists such as T.H. Green and John Dewey, as well as between the liberal and socialist traditions. Not only does it break new ground in its demonstration of the complementary relationship between freedom and power, it is the first comprehensive study of Mill's social and political thought that seriously engages his feminism